The role of total ankle replacement in patients with haemophilia and end‐stage ankle arthropathy: A review. Issue 2 (8th November 2020) - Sackstein, Paul; Cooper, Paul; Kessler, Craig
Abstract: Haemophilia is the most common X‐linked bleeding disorder, affecting over 1 million individuals throughout the world. Patients are subclassified into mild, moderate and severe disease based on per cent factor activity level. Nearly, all patients with haemophilia develop haemophilic arthropathy (HA) by age 30 and HA is known to have a negative impact on physical health subscores in Haem‐A‐QOL, a validated quality of life scoring system for patients with haemophilia. Unfortunately, many patients progress to end‐stage HA of the ankle, which is characterized by pain, contractures, decreased range of motion and muscle atrophy. Ankle arthrodesis (AAD) has been the standard of care in the definitive surgical management of end‐stage HA of the ankle. While AAD is a safe surgical procedure known to improve HA‐related pain, it decreases functional mobility and has been associated with secondary hindfoot arthritis as well as subtalar degeneration. In recent years, total ankle replacement (TAR) has emerged as an alternative surgical procedure that strives to improve functional mobility, pain and quality of life in end‐stage HA of the ankle. However, the safety, durability, and efficacy of this procedure in these patients are unknown. In this review, we analyse the clinical studies investigating TAR in patients with end‐stage HA of the ankle. We also discuss important considerations in the perioperative management of patients with haemophilia and compare the risks and benefits of AAD and TAR for patients with end‐stage HA of the ankle.